Pulmonary fibrosis following therapy with Melphalan for multiple myeloma - Codling, B. W. (1972)
A patient suffering from multiple myeloma developed pulmonary fibrosis, of a type known to be associated wtih busulphan, whilst being treated with Melphalan. The possible role of Melphalan as the causative agent is discussed. Reference is made to other possible aetiological agents and the reasons for their exclusion are discussed.